Regulatory Frameworks for Orphan Medical Device: A Comparative Review of USFDA and EU Approaches - KUBERAN S; KAMARAJ R (The Bioscan, 2025)
Approval and development of medical products dealing with rare illnesses, referred to as orphan devices, present special regulation and clinical issue because of small patient requirements, significant development expenses, and low commercial appeal. The paper entails a comparative evaluation of the regulatory standards implemented by the United States food and drug administration (USFDA) as well as the European Union (EU) in dealing with these challenges. The USFDA has now created specific methods to accelerate orphan devices with their Humanitarian Use Device (HUD) and Humanitarian Device exemption (HDE) programs, which have more relaxed standards of clinical evidence and ease of entry of an orphan to the market by utilizing Institutional Review Board (IRB)-approved use. By comparison, the EU covers the subject of orphan devices with the Medical Device Regulation (MDR) 2017/745, not giving them a specific orphan pathway, which requires a stricter procedure of conformity assessment and increased amount of premarket clinical evidence. This paper presents the definitions, the approval methods, post-marketing surveillance requirements, and challenges peculiar to each of the regions. Although the US system focuses on faster access among limited data, the EU system prefers high safety and performance requirements. The review comes to the conclusion that harmonization, or mutual learning of these regulatory systems, may promote both innovation and patient safety especially concerning the SMEs and patients with rare medical conditions.